Legal Certainty of Nominee Agreements In The Transfer of Ownership Rights To Land Based on An Absolute Letter of Power - Dyah Pertiwi, Meliana; Grahani Firdausy, Adriana; Budi Kharisma, Dona (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Article 21 of Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA) also states that those entitled to Property Rights are Indonesian Citizens and Legal Entities appointed by the Government. However, in fact, there are still many practices of Nominee agreements based on absolute power of attorney to avoid these legal restrictions in order to disguise ownership of land. The urgency of this research is the importance of studying the legal certainty of nominee agreements based on absolute power of attorney. In this legal research, the normative and prescriptive legal research methods are used. In this legal research, the author uses a statutory regulatory approach, a conceptual approach and a case approach. The author utilizes primary and secondary legal materials. Data collection techniques in this research are carried out through literature studies. In this legal research, the Legal Material Analysis Technique is used with the Syllogism Method, which is a deductive way of thinking that applies logical principles to reach conclusions based on general and specific premises. Nominee agreements based on absolute power of attorney, based on the valid conditions of the agreement in Article 1320 of the Civil Code, have violated the lawful purpose because they disguise the original ownership of the land object and constitute legal smuggling. Instruction of the Minister of Home Affairs Number 14 of 1982 concerning the Prohibition of the Use of Absolute Power of Attorney as a Transfer of Land Rights expressly prohibits the use of absolute power of attorney to transfer or disguise ownership of land rights. In this case, a name borrowing agreement in the transfer of land ownership rights based on an absolute power of attorney, which does not comply with the rules or laws, does not provide legal certainty for the holder of the letter.